SYNTHESIS AND EVALUATION OF SCHIFF BASE COMPOUNDS AS COPPER AND NICKEL CHELATORS AND RADICAL SCAVENGERS.: SÍNTESE E AVALIAÇÃO DE COMPOSTOS DE BASE DE SCHIFF COMO QUELANTES DE COBRE E NÍQUEL E SEQUESTRADORES DE RADICAIS - Chagas da Silveira, Vivian; Costa Cabral Salazar Ramos Moreira, Kelly; Ferreira Martins, Lucas; Mapheu Nogueira, Christiane; Oliveira Costa, Ana Paula; Furlan Mendes, Ana Nery (Brazilian Journal of Production Engineering, 2020)
Several process involving oxidative reactions have a great importance in our routine. Since the antioxidants are very important in diverse industrial areas, three Schiff base compounds were synthetized, characterized (ovalen, valen and dhben) and evaluated for the antioxidant potential acting as radical scavengers and as chelators of transition metals. Their stability constants with Ni(II) and Cu(II) ions were calculated and their antioxidative capacity were determinated by a chelating activity assay and a DPPH method. Dhben shows a greater ability in chelating copper ions than nickel ions in low Schiff base concentrations. Ovalen is also a great chelating agent, being better with nickel than with copper. The results agree with the obtained binding constants 9,09 X 102 L mol-1 for [Cu-dhben] and 9,91 X 102 L mol-1 for [Ni-ovalen]. In DPPH assay, it was observed that dhben and ovalen were capable to decrease DPPH absorbance concentration, however dhben could reach the IC50 even low concentrations. Both dhben and ovalen are good copper and nickel chelating agents, but when it is about free radicals, dhben is the best agent.